2017
DOI: 10.3126/jcmsn.v13i3.17694
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension and Diabetes Mellitus in Political Cadres of Nepal

Abstract: Background & Objectives: Hypertension and Diabetes Mellitus are both major modifiable risk factors leading to premature death due to cardiovascular and cerebrovascular diseases. Therefore, early diagnosis and treatment are must to reduce morbidity and mortality due to following diseases. Therefore authentic data on these issues are of great importance. The aim of this study was to address this gap and create awareness regarding essence of control of Diabetes and Hypertension among political cadres of Nepal as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…11 The prevalence of high blood pressure was 44.32% in political cadres and 41.9% in police personnels. 12,13 Similar results of lower prevalence of hypertension in army population (9.7%) than general population is reported by another study done in Brazilian army. 14 From these studies of different occupational groups, it is seen that the prevalence of HTN is considerably lower in military personnel than the general occupation-related lifestyle, as military personnel are activities, regular exercise, and health screening at entry.…”
Section: Discussionsupporting
confidence: 75%
“…11 The prevalence of high blood pressure was 44.32% in political cadres and 41.9% in police personnels. 12,13 Similar results of lower prevalence of hypertension in army population (9.7%) than general population is reported by another study done in Brazilian army. 14 From these studies of different occupational groups, it is seen that the prevalence of HTN is considerably lower in military personnel than the general occupation-related lifestyle, as military personnel are activities, regular exercise, and health screening at entry.…”
Section: Discussionsupporting
confidence: 75%
“…This study established the prevalence of diabetes among university staff as 16.1%, this finding is not much different from 15% prevalence in Nepal among people aged 20 years and above according to Nepal Diabetes Association (NDA) [25]. In contrast however, cross-sectional studies previously done around towns close to Kampala city showed a low prevalence of 8.1% [26] and 9% from studies on foot hills of Rwenzori Mountains in western Uganda [13].…”
Section: Diabetesmentioning
confidence: 69%
“…19,20 *significant p value < 0.05 in Southwest Ethiopia 6.5%, 21 in Saudi 2279 (30%), 6 10% in India, 22 in Eastern Nepal 26.3% 23 and in Kathmandu 18.56%. 17 This discrepancy may be due to differences in the study area, study designs, sample sizes used, and the year the studies were conducted. The prevalence of diabetes is increasing day by day in Nepal may be due to urbanization.…”
Section: Discussionmentioning
confidence: 99%
“…The method of blood pressure measurement and criteria for diagnosis of hypertension was done according to JNC VII guidelines that is, systolic blood pressure (SBP) ≥ 140 mm Hg or diastolic blood pressure (DBP) ≥ 90 mm Hg and/or concomitant use of antihypertensive medications. 16 Sample size was calculated using formula Z 2 pq/d 2 , where (p) was taken as 18.5% 17 As shown in table 6, the prevalence of DM was almost same in both males 13 (52.0%) and females 12 (48.0%). DM was seen more in subjects who had completed secondary level education 11 (44.0%) , who were homemakers and government job holders, 3 (33.3%) each and who were prehypertensive 13 (52.0%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation